Pengaruh Pemberian Kompos Eceng Gondok Dan Purun Tikus Terhadap Pertumbuhan Dan Produksi Tanaman Terong Ungu (Solanum Melongena L) - Iswahyudi, Herry; Fahmi, Fahmi; Indriani, Indriani (Universitas Lambung Mangkurat, 2024)
Water hyacinth (Eichhornia crassipes) and Purun tikus (Eleocharis dulcis) plants are commonly found in rice fields, especially in South Kalimantan, where they act as weeds in the main crop. However, these plants can be utilized as compost to enhance soil nutrients for crops. This study aims to evaluate the effect of compost derived from water hyacinth, Purun tikus, and their combination on the growth and yield of purple eggplant (Solanum melongena). The study uses a Randomized Block Design (RBD) method with four treatments, each repeated six times, resulting in 24 experimental plants as follows: P0 = no treatment (control), P1 = 900 g water hyacinth compost, P2 = 900 g Purun tikus compost, and P3 = a combination of 450 g water hyacinth compost and 450 g Purun tikus compost. The results indicated that, for plant height, treatment P3 yielded an average of 53.61 cm; for leaf count, treatment P3 produced an average of 45.66 leaves; for stem diameter, treatment P1 achieved an average of 9.90 mm; for fruit count, treatment P3 showed an average of 2.16 fruits; and for fresh fruit weight, the best result was achieved by treatment P3, with an average weight of 145.83 g